Redesain Pasar Panakkukang dengan Pendekatan Arsitektur Modern di Kota Makassar - Syahmila Putri, A.Rania; Bunawardi, Ratriana Said; Juddah, Safruddin (TIMPALAJA : Architecture Student Journals, 2025)
Problems at Panakkukang Market stem from declining environmental quality, irregular circulation, and a lack of supporting facilities, leading to poor comfort for visitors and vendors. This situation indicates the need for redesign efforts to enable the market to function more optimally as a center of community economic activity. The purpose of this study is to redesign Panakkukang Market by applying Type III traditional market standards, modern architectural principles that emphasize functionality and spatial efficiency, and integrating local cultural values to strengthen the area’s identity. The methods used include primary data collection through field observations and interviews, and secondary data through literature studies and precedent studies of similar projects. The design results demonstrate a more organized zoning, the implementation of a one-way circulation pattern to improve movement, and facade and interior design that prioritizes natural lighting, spatial flexibility, and the use of geometric modules. The integration of local concepts enriches the visual character and meaning of the space, thereby improving market function, user comfort, and the overall attractiveness of the environment.